O papel da produção da habitação social em São José do Rio Preto na consolidação do dispositivo Zona Norte - Ueda, Poliana Risso Silva (2021)
The present work aims to contribute to the knowledge base on the socio-spatial production of the urban space in non-metropolitan cities, by studying the formation process of the North Zone territory, in the city of São José do Rio Preto. The thesis seeks to investigate, through the analysis of the historical trajectory of the social housing production in the city, the processes through which the northern area of the city becomes a place of socio-spatial segregation, highlighting the transformations it has undergone due to the activity of the capital. More than that, it aims to identify, in time and space, the historical elements that contributed to the consolidation of the Northern area as the territory of a new centrality, both from an external reading, that of the housing production inserted in a capitalist accumulation system, and from an internal, qualitative view. For the investigation, three methodological strategies were adopted, which involve: research in primary sources, based on data and documents provided by government agencies, statistical bases and newspapers; in secondary sources, in the vast existing literature on the urban theory to form the theoretical basis of research; and semi-structured interviews with individuals who received the benefits of the housing programs and are currently living in the region. The theoretical framework allowed an analysis of the socio-spatial organization of the territory as a result of the production process of social housing in the city, the role of the State and real estate agents in shaping the North Zone and the socioeconomic scenario and social relations that weave the lived space. The understanding is that these elements have made this new centrality become a government device of great power. A possible solution would require building new subjectivities that allowed the coproduction of the urban spaces by different subjects, as a path to achieve the process of re-valorization of political actions, leading to the rupture with current order.